網路學生出題策略應用於國小古典詩課程其成效之研究 Effects of Online Student Question-Generation on Primary School Classic Chinese Poetry Instruction - 邱廷榮 Ting-Jung Chiu; 于富雲 Fu-Yun Yu (National Taiwan Normal University, 2011)
本研究旨在探究網路學生出題策略應用於國小古典詩課程對學習成就、學習動機與上課情意之影響。本研究採準實驗研究設計法，受試者為屏東縣某一國小六年級共三班學生（共100 人），分為網路學生出題實驗組（68 人）與傳統學習單習寫對照組（32 人）。實驗教學前進行前測，5 週實驗課程後再進行後測。資料以單因子共變數分析以及成對樣本t檢定進行分析。主要研究發現：一、實驗組在學習成就、學習動機與上課情意上顯著優於對照組；二、實驗組能有效提升受試者的學習動機與上課情意。文末，根據研究發現提出教學與未來研究之建議。 This study investigates the comparative effects of an online student question-generation strategy against the use of traditional worksheets on student academic performance, learning motivation and attitudes toward classic Chinese poetry using a quasi-experimental research design. Three 6th-grade classes (N=100) participated in the study and were randomly assigned to the experimental group (2 classes, N=68) and the control group (N=32). Several findings were obtained. First, analysis of covariance indicated that students in the online student question-generation group scored significantly higher than those in the traditional worksheet group in academic performance, learning motivation and attitudes toward class, compared to those in the contrast group. Second, a paired sample t test revealed that the learning motivation and attitudes toward class for the online student question-generation group significantly improved after the question-generation experience. Finally, the learning motivation for the worksheet group significantly lowered after the treatment. Suggestions for instructional practices and future studies are provided.